Answer:
1. - 2, 1
2. S = -2 + -2 = -4
P = (-2) (-2) = 4
3. S = -b/a
= -(-3)/1
= 3
P = c/a
= 9/1
= 9
4. S = -b/a
= -2/5
P = c/a
= -3/5
5. S = -b/a
= -(-6)/2
= 3
P = c/a
= 1/2
Step-by-step explanation:
1. x^2 + 2x + 1 = 0
a = 1; b = 2; c = 1
sum of the roots: -b/a
-b/a
-2/1 = -2 is sum of the roots
product of the roots: c/a
c/a
1/1 = 1 is product of the roots
2. x^2 + 4x + 4 = 0
(x + 2) (x + 2)
x + 2 = 0 0r x + 2 = 0
x = -2 x = -2
S = -2 + -2 = -4
P = (-2) (-2) = 4
3. x^2 - 3x + 9
a = 1; b = -3; c = 9
S = -b/a
= -(-3)/1
= 3
P = c/a
= 9/1
= 9
4. 5x^2 + 2x - 3 = 0
a = 5; b = 2; c = -3
S = -b/a
= -2/5
P = c/a
= -3/5
5. 2x^2 - 6x + 1
a = 2; b = -6; c = 1
S = -b/a
= -(-6)/2
= 3
P = c/a
= 1/2
sana makatulong